PARTNERSHIP-BASED TEACHING FACTORY LEARNING - Tho'at Tho'at (Universitas Muhammadiyah Semarang, 2018)
This research aims to describe and analyze the planning, organizing, implementing and monitoring of the partnershipbasedteachingfactory in SMK NU Ma'arif Kudus. This research is a qualitative research using case study approach. Thesubjects of the research were determined purposively including principal, vice principal, skill program chiefs, chairmen /TEFA Managers, some productive teachers, students and representatives from industry partners. Data collection techniquesused in-depth interviews, observations and document studies. Data analysis used Milles & Huberman model that is datacollection, data reduction, data display and conclusion. The results of the research are as follows: 1) TEFA planning carriedout jointly by SMK and industry (PT.ADMI) through synchronization and integration of curriculum contents with industryneeds. 2) Organizing is done collaboratively by providing the role of industry representatives & teachers as consultants,assessors and facilitators. While the students there acted as manager, administration, production and MR. 3) Theimplementation of TEFA is implemented by the students in their respective roles and positions in accordance withestablished standard procedures and receiving guidance / consultation from industries and productive/ practices teachers bycreating an atmosphere / replica of actual industry work. 4) Supervision is done jointly by the School and industry throughadministrative and non-administrative approaches to ensure the implementation of activities in accordance withpredetermined plans. Keywords: Learning, Teaching Factory (TEFA), partnerships, vocational schools (SMK)